Fracture strength of laminate veneers using different restorative materials and techniques (A comparative in vitro stuy) - Abdul Khaliq, Abeer Gh; Al-Rawi, Inas I (Journal of Baghdad College of Dentistry, 2014)
Background: Esthetic correction represents one of the clinical conditions that required the use of laminate veneers in premolars region. Aim of the study: The purpose of this study was to evaluate the fracture strength of the laminate veneers in maxillary first premolars, fabricated from either composite (direct and indirect techniques) or ceramic CAD/CAM blocks. Materials and Methods: Fifty sound human maxillary premolar teeth were used in this in vitro study. Teeth were divided randomly into one control group and four experimental groups of ten teeth each; Group A: Restored with direct composite veneer (Filtek Z250 XT), Group B: Restored with indirect composite veneers (Filtek Z250 XT), Group C: Restored with lithium disilicate ceramic CAD/CAM blocks (IPS e. max CAD) and Group D: Restored with resin nano ceramic CAD/CAM blocks (Lava Ultimate Restorative). Standard preparations were done using Ceramic Veneer Set (Komet). Indirect laminate veneers were cemented with the Relyx Veneer Cement (3M ESPE) and all specimens were stored in distilled water at 37Â°C for 2 weeks. The load was applied on the occlusal part of the veneer at 45Ëš to long axis of the tooth using universal testing machine. Results were analyzed with one-way ANOVA and LSD tests. Specimens were examined by stereomicroscope at a magnification of 20x to evaluate the mode of failure. Results: Control group showed higher mean of fracture strength with highly significant difference in comparison to the experimental groups (P